2016
DOI: 10.1038/nchembio.2017
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Aurora B by TIP60 ensures accurate chromosomal segregation

Abstract: Faithful chromosome segregation in mammalian cells requires the bi-orientation of sister chromatids which relies on sensing correct attachments between spindle microtubules and kinetochores. Although the mechanisms underlying cyclin-dependent kinase 1 (CDK1) activation that triggers mitotic entry is extensively studied, the regulatory mechanisms that couple CDK1-cyclin B activity to chromosome stability are not well understood. Here, we identified a signaling axis in which Aurora B activity is modulated by CDK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 50 publications
6
99
0
Order By: Relevance
“…1F, FLAG-Sds22 proteins were immunoisolated from DMSO-and BI 2536-treated HeLa cells. Sds22 protein bands, from DMSO-and BI 2536-treated cells, were removed for ingel digestion followed by mass spectrometric identification (12 Phosphorylation of Sds22 Is Critical for Accurate Mitotic Progression-To examine the role of PLK1-mediated phosphorylation of Sds22 in mitosis, we generated non-phosphorylatable and phosphomimetic Sds22 mutants tagged with GFP, which were transiently transfected into HeLa cells together with mCherry-H2B. Comparison of expression levels of exogenous and endogenous Sds22 were shown in Fig.…”
Section: Plk1 Interacts With and Phosphorylatesmentioning
confidence: 99%
See 1 more Smart Citation
“…1F, FLAG-Sds22 proteins were immunoisolated from DMSO-and BI 2536-treated HeLa cells. Sds22 protein bands, from DMSO-and BI 2536-treated cells, were removed for ingel digestion followed by mass spectrometric identification (12 Phosphorylation of Sds22 Is Critical for Accurate Mitotic Progression-To examine the role of PLK1-mediated phosphorylation of Sds22 in mitosis, we generated non-phosphorylatable and phosphomimetic Sds22 mutants tagged with GFP, which were transiently transfected into HeLa cells together with mCherry-H2B. Comparison of expression levels of exogenous and endogenous Sds22 were shown in Fig.…”
Section: Plk1 Interacts With and Phosphorylatesmentioning
confidence: 99%
“…During mitotic spindle assembly, centromere-localized Aurora B destabilizes kinetochore-microtubule interactions that are under low mechanical tension (2,9) by phosphorylating several components of the outer kinetochore, including NDC80/Hec1, KNL-1, and Dsn1 (3,10). The Aurora B-mediated error correction is important for bipolar attachment of all chromosomes, which satisfies the SAC to initiate anaphase (11,12).…”
mentioning
confidence: 99%
“…DNA was stained with DAPI (Sigma). Images were acquired with a DeltaVision wide-field deconvolution microscope (Applied Precision Inc.) as described previously (44). For single cell migration, MDA-MB-231 cells were cultured in a glass-bottom culture dish (MatTek).…”
Section: Methodsmentioning
confidence: 99%
“…The critical role of K134 Ran in binding to Mog1 prompted us to conduct computational analyses for lysine acetylation (Li et al, 2006), which suggested K134 Ran as a potential substrate of TIP60 (Mo et al, 2016). Given our recent demonstration that TIP60-dependent acetylation is critical for accurate chromosome segregation in mitosis (Mo et al, 2016), we postulated that TIP60 may acetylate K134 Ran to retain a dynamic Ran–Mog1 interaction for accurate kinetochore-microtubule interactions in mitosis. Specifically, our structural analyses suggest that persistent acetylation of K134 Ran would disrupt the Ran–Mog1 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings provide structural delineation of molecular mechanism by which post-translational modifications could yield sharp transitions between functionally distinct Ran-GTPase states, generating nonlinearity in Ran signaling cascades, and contributing to the spindle plasticity control during cell division cycle. It is worth noting that TIP60 localization depends on Ndc80 (Mo et al, 2016), and TIP60-elicited acetylation of Ran would provide centromere-based spatial control of Ran-GTP gradient centered on kinetochore (Figure 6G). Thus, our study points to an intricate cross-talk among Cdk1, TIP60, Ndc80, and Ran-GTPase in sensing kinetochore-microtubule attachment.…”
Section: Discussionmentioning
confidence: 99%